2010
DOI: 10.4314/ajbr.v10i3.50654
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and potential anticarcinogenic activities of aloe-vera gel and aqueous garlic extract in the bacterial reverse mutation test (ames assay)

Abstract: The study was carried out to verify the potential anticarcinogenic and antimutagenic activity of garlic and aloe-vera. The ability of aqueous garlic extract and Aloe-Vera gel to inhibit mutation in tester strain of Escherichia coli WP2 uvrA was determined in this study. (The tester E. coli tryptophan auxotroph strain was obtained from Yale University U.S.A.).The spontaneous mutation rate of E. coli WP 2 uvrA was determined in the Ames assay to be 2.2 x 10 -7 . The acridine mutagen showed 333.8% increase of spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Previously, antigenotoxicity of gel extract of A. vera against genotoxicity of a direct mutagen (ethylmethanesulphonate) induced in Drosophila melanogaster following the Drosophila sex linked recessive lethal test was reported (Snežana, 2007). Ogunjobi et al (2007) also reported antimutagenic and anticarcinogenic activity of aqueous garlic extract and A. vera gel extract inhibiting acridine dye -inducing mutation in the tester strain Escherichia coli WP2 uvrA. In the present study, our results have also confirmed antigenotoxic potency of A. vera gel extract against sodium azide.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, antigenotoxicity of gel extract of A. vera against genotoxicity of a direct mutagen (ethylmethanesulphonate) induced in Drosophila melanogaster following the Drosophila sex linked recessive lethal test was reported (Snežana, 2007). Ogunjobi et al (2007) also reported antimutagenic and anticarcinogenic activity of aqueous garlic extract and A. vera gel extract inhibiting acridine dye -inducing mutation in the tester strain Escherichia coli WP2 uvrA. In the present study, our results have also confirmed antigenotoxic potency of A. vera gel extract against sodium azide.…”
Section: Discussionsupporting
confidence: 88%
“…The biological effects of AO, which includes photodynamic and mutagenic actions of the dye, constitute another large area of research [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…There is a high correlation between carcinogenicity and mutagenicity. Most studies related to antimutagenic activity has been focused on identifying naturally occurring chemo-preventing substances capable of inhibiting, retarding or reversing the multistage carcinogenesis 1 .…”
Section: Introductionmentioning
confidence: 99%